The Effect Of Using Leaf Media To Improve Fine Motor Skills Of 4-5 Year Old Children At RA Smart Hafizh School Batam City - Alif Laini; Nurhayati, Nurhayati; Ayu Citra Dewi; Selpi Indramaya (International Journal of Education, Vocational and Social Science, 2024)
The problem raised in this study is the effect of using leaf media in improving children's fine motor skills at RA Smart Hafizh School Batam City. The purpose of this study was to determine the effect of using leaf media in improving children's fine motor skills at RA Smart Hafizh School Batam City. In this study, researchers used a type of quantitative research with an experimental method that was "quasi-experimental Desigh" type "posttest-only Control Design". the population used in this study took a sample of 4-5 year old children at RA Smart Hafizh School Batam City which was used as an experimental class with a total of 16 children, and children at RA An Nisaa which was used as a control class. with a total of 15 children. With the number of children 15 children. The sampling technique used is purposive sampling. From the results of the study it can be concluded that the results of the paired samples test on the experimental class pre test data with the experimental class post test obtained a value of p = 0.000 <0.05, which means that there is an effect of using leaf media to improve the fine motor skills of 4-5 year old children at RA Smart Hafizh School Batam City.